Do farmers support cheetah Acinonyx jubatus conservation in Botswana despite livestock depredation? - Selebatso, Moses; Moe, Stein R.; Swenson, Jon E. (Oryx, 2008)
In Botswana a large cheetah population, with higher densities outside than inside protected areas, increases the potential of conflict with farmers because of livestock depredation. However, information on the extent of livestock depredation by cheetah and farmers’ perceptions of this has been lacking. We interviewed 123 farmers in Ghanzi District, Botswana, to assess problems caused by cheetah depredation of livestock and farmers’ attitudes towards cheetah conservation beyond protected areas. Despite livestock losses, farmers generally supported efforts to conserve cheetah, with support increasing with level of education. However, farmers felt that cheetah should not be conserved within farming areas. Land-use practice and culture related to land use played a major role in determining the level of farmers’ support for cheetah conservation beyond protected areas: high on private farms, moderate in wildlife management areas, and low on communal lands. Underreporting by farmers led to underestimation by the Department of Wildlife and National Parks of the extent and nature of cheetah conflict with farmers. This study suggests that education and active involvement of farmers in planning and decision-making concerning cheetah management would enhance farmers’ positive perception of cheetah conservation beyond protected areas.